Ahr and CYP1B1 gene expression in type 2 diabetes patients in Vietnam - Duc, Le Hoang; Trung Nam, Nguyen (Vietnam Journal of Biotechnology, 2021)
Type 2 diabetes is a chronic disease, which has risen dramatically in many countries in the world, including Vietnam. Recently, there is increasing evidence about the link between type 2 diabetes and the exposure to Ahr ligands such as 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in the experimental animal model. In the cell, after activation by the ligands, Ahr moves from the cytoplasm into the nucleus and binds to the nuclear translocator, resulting in transcription of target genes such as Cyp1b1. The development of type 2 diabetes was shown in some people who exposed to TCDD. However, the role of Ahr/Cyp1b1 genes in type 2 diabetes patients has not been elucidated. In this study, the expression of the Ahr and Cyp1b1 genes in blood samples collected from patients with type 2 diabetes and controls was studied for the first time in Vietnam. Analysis of blood glucose showed that this index in the type 2 diabetes patients was higher than that in the control group. Using real-time PCR method, the results showed that the expression of Ahr and Cyp1b1 in type 2 diabetes patients was significantly higher than that in control group. In addition, the expression of Ahr and Cyp1b1 was positively correlated with the blood glucose levels of both groups. These results are initial evidence for the link between activation of Ahr/Cyp1b1 signaling pathway and level of blood glucose so that Ahr/Cyp1b1 genes can be potential targets to treat type 2 diabetes.